2019
DOI: 10.1038/s41438-018-0116-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide comprehensive analysis of transcriptomes and small RNAs offers insights into the molecular mechanism of alkaline stress tolerance in a citrus rootstock

Abstract: Alkaline stress has serious-negative effects on citrus production. Ziyang xiangcheng ( Citrus junos Sieb. ex Tanaka) (Cj) is a rootstock that is tolerant to alkaline stress and iron deficiency. Trifoliate orange ( Poncirus trifoliata (L.) Raf.) (Pt), the most widely used rootstock in China, is sensitive to alkaline stress. To investigate the molecular mechanism underlying the tolerance of Cj to alkaline stress, next-generation sequencing was employed to profile the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 76 publications
(88 reference statements)
0
21
0
Order By: Relevance
“…Rootstock is an important part of the Citrus industry as it influences scion characteristics such as fruit quality, canopy size, and resistance 8,9 . Previous studies have demonstrated that Citrus -grafted seedlings with Pt as rootstock were prone to nutrient deficiency and growth retardation in calcareous soils 10,11 . However, Ziyang xiangcheng ( Citrus junos Sieb.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rootstock is an important part of the Citrus industry as it influences scion characteristics such as fruit quality, canopy size, and resistance 8,9 . Previous studies have demonstrated that Citrus -grafted seedlings with Pt as rootstock were prone to nutrient deficiency and growth retardation in calcareous soils 10,11 . However, Ziyang xiangcheng ( Citrus junos Sieb.…”
Section: Introductionmentioning
confidence: 99%
“…However, Ziyang xiangcheng ( Citrus junos Sieb. ex Tanaka) (Cj) is a local Citrus rootstock originating from Southwest China with excellent disease-, alkali-, drought-, and cold-resistant characteristics 10 . Additionally, Cj is more alkali-resistant than Pt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Citrus is a woody perennial plant, and it is widely planted all over the world in a form of graft. For instance, the commercial citrus cultivars Newhall sweet orange and Mandarin as scion are grafted onto the rootstocks Poncirus and Citrange , which is of significant importance for increasing the fruit’s quality and its resistance to multiple biotic and abiotic stresses [ 48 , 49 , 50 , 51 , 52 ]. However, how scion and rootstock combinations affect the AMF community in citrus roots is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Applying exogenous substances effectively alleviates salt stress [29]. These substances are commonly divided into the following three categories: The first category is the plant growth regulators, such as jasmonate (JA), cytokinin (CTK), and abscisic acid (ABA) [4,30,31]. JA has a positive regulatory role in plant resistance to salt stress, and its exogenous application can improve the salt tolerance of Arabidopsis, tomatoes, and rice [32,33,34].…”
Section: Introductionmentioning
confidence: 99%